2015
DOI: 10.1128/ec.00141-14
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Lipid Droplet Proteome of the Oleaginous Yeast Rhodosporidium toruloides

Abstract: c Lipid droplets (LDs) are ubiquitous organelles that serve as a neutral lipid reservoir and a hub for lipid metabolism. Manipulating LD formation, evolution, and mobilization in oleaginous species may lead to the production of fatty acid-derived biofuels and chemicals. However, key factors regulating LD dynamics remain poorly characterized. Here we purified the LDs and identified LD-associated proteins from cells of the lipid-producing yeast Rhodosporidium toruloides cultured under nutrient-rich, nitrogen-lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 70 publications
(134 reference statements)
4
73
0
2
Order By: Relevance
“…Proteomic studies showed that it is a highly abundant protein during lipid accumulation phase [5]. Likewise, the α and ÎČ subunits of fatty acid synthase (Fas2 and Fas1, respectively), fatty acid transporter (Fat1), ATP:citrate lyase (Acl1) and urea carboxylase/allophanate hydrolase (Dur1/2) were also found in high abundance during lipid accumulation phase [14, 15]. Other known abundant targets are the p erilipin, a dipophilin and t ail-interacting (PAT) family proteins, which serve as dynamic scaffolds regulating the formation, growth and degradation of lipid bodies [15–19].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic studies showed that it is a highly abundant protein during lipid accumulation phase [5]. Likewise, the α and ÎČ subunits of fatty acid synthase (Fas2 and Fas1, respectively), fatty acid transporter (Fat1), ATP:citrate lyase (Acl1) and urea carboxylase/allophanate hydrolase (Dur1/2) were also found in high abundance during lipid accumulation phase [14, 15]. Other known abundant targets are the p erilipin, a dipophilin and t ail-interacting (PAT) family proteins, which serve as dynamic scaffolds regulating the formation, growth and degradation of lipid bodies [15–19].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the lipid-dropletassociated proteins, a core set of about 50 proteins has been found to decorate lipid droplets in various cellular systems (reviewed in Hodges and Wu, 2010). However, a diverse and large number of additional proteins has been identified across many studies (a selection of studies is given in Beilstein et al, 2013;Beller et al, 2006;Cermelli et al, 2006;Chen et al, 2016;Currie et al, 2014;Dahlhoff et al, 2015;Ivashov et al, 2013;Khan et al, 2015;Khor et al, 2014;Krahmer et al, 2013;Li et al, 2016;Na et al, 2013;Schmidt et al, 2013;Su et al, 2014;Zhang et al, 2011;Zhu et al, 2015), suggesting a significant amount of variability in terms of the lipid droplet protein composition between lipid droplets isolated from different cell types.…”
Section: Are All Lipid Droplets the Same?mentioning
confidence: 99%
“…More recently, systematic studies on the poorly characterized organelles in oleaginous microorganisms [termed lipid droplets (LDs) or lipid particles (LPs)], have been demonstrated using proteome analysis. Studies in the lipid-producing yeast, Rhodosporidium toruloides, indicated that the LD proteome consists of 226 proteins, 11 of which were annotated as lipid-degrading enzymes (Zhu et al 2015). From that study, the orthologue of the bifunctional enzyme, Tgl5 (RHTO_03931), which has triacylglycerol lipase and lysophosphatidic acid acyltransferase activities, were identified, suggesting that the enzyme could promote LD fusion to generate larger LDs (Fei et al 2011;Yang et al 2012).…”
Section: Omic Data Analysis For Microbial Lipid-degrading Enzymesmentioning
confidence: 97%
“…From that study, the orthologue of the bifunctional enzyme, Tgl5 (RHTO_03931), which has triacylglycerol lipase and lysophosphatidic acid acyltransferase activities, were identified, suggesting that the enzyme could promote LD fusion to generate larger LDs (Fei et al 2011;Yang et al 2012). However, the orthologue of the mammalian hormone-sensitive lipase (RHTO_02359) was absent in the LD proteome, suggesting that it was not recruited at the lipid accumulation stage (Zhu et al 2015). In addition, proteomic approaches could reveal an enzyme candidate missing in the target pathway.…”
Section: Omic Data Analysis For Microbial Lipid-degrading Enzymesmentioning
confidence: 99%